â€œGundalaâ€ an Indonesian Superhero Film and Its Influence on Audiencesâ€™ National Identity - Sutanto, Marisa Rianti; Kosasih, Marcella Melly (Bina Nusantara University, 2023)
The research aimed to find out and prove the impact of the film Gundala on its audienceâ€™s sense of national identity. The research was conducted by using the method of audience reception. The target audience of the survey was people who belong to the young adult category called Generation Z. The survey was conducted through the distribution of a seven-question questionnaire, and data were obtained from 53 respondents. The questions were designed according to the expression of four aspects reflected in the film plot: character, accessories, ethnoscape, and community. The results of the questionnaire data are presented through frequency distribution tables, measured according to Likert scale positive statements. Based on the survey results, the Generation Z audience has an awareness of national identity reflected in the film â€œGundalaâ€. The results of the qualitative analysis of the questionnaire data show that the film â€œGundalaâ€ has a minor but discernible impact on the audienceâ€™s sense of national identity.